Role of Mesenchymal Stem Cells In Chronic Obstructive Lung Disease - Fatmi Andari; Triya Damayanti (Respiratory Science, 2021)
Therapy for Chronic Obstructive Pulmonary Disease (COPD) is currently still not giving effect to tissue repair and regeneration. Chronic Obstructive Pulmonary Disease is still a progressive degenerative disease. Stem cells through their regenerative ability offer a new promising alternative therapy for the management of degenerative diseases including COPD. There have been many studies conducted to determine the safety and efficacy of stem cells in COPD. Published research about stem cells on COPD is still in phase II. Further research is needed on a larger scale before stem cells can be widely applied in the management of COPD. Stem cells are a very promising alternative therapy and are a big leap in the medical world for degenerative diseases including COPD.